Assessing the Role of Tourism Facilities in Shaping Visitor Interest: Evidence from Loang Baloq Beach, Mataram - Nur Haj, Harfi; Idrus, Syech; Suteja, I Wayan (Advances in Tourism Studies, 2025)
This study investigates the influence of tourism facilities on visiting interest at Loang Baloq Beach, Mataram, Indonesia, with visitor satisfaction as a mediating variable and destination image as a moderating factor. Drawing on the Stimulus–Organism–Response and Theory of Planned Behavior frameworks, a quantitative explanatory design was employed using data collected from 175 visitors through structured questionnaires. The measurement and structural models were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that tourism facilities significantly and positively affect visitor satisfaction and visiting interest, while satisfaction also mediates the relationship between facilities and behavioral intention. Furthermore, destination image strengthens the relationship between facilities and satisfaction, demonstrating its moderating influence. These findings highlight that facility quality contributes not only to functional satisfaction but also to the emotional and perceptual dimensions of visitor experience. The study confirms that destination competitiveness is shaped by the interplay of physical infrastructure, visitor satisfaction, and image perception. For policymakers and tourism managers, the results emphasize the importance of integrating facility improvement with destination branding and service quality enhancement to sustain visitor loyalty. The study contributes theoretically by validating a moderated mediation framework that explains behavioral intention in urban coastal tourism settings.